A Novel Small Molecule, LCG-N25, Inhibits Oral Streptococcal Biofilm - Lyu, Xiaoying; Li, Chungen; Zhang, Jin; Wang, Liang; Jiang, Qingsong; Shui, Yusen; Chen, Lan; Luo, Youfu; Xu, Xin (Frontiers in Microbiology, 2021)
Dental caries is a chronic oral infectious disease caused by cariogenic biofilm adhered on the tooth surface. Our previous study demonstrated that a repurposed natural compound napabucasin showed good antimicrobial activity against oral streptococcal biofilms. The current study designed a novel small molecule, namely LCG-N25, using napabucasin as a lead compound, and aimed to investigate its potential as an antimicrobial agent in the control of dental caries. LCG-N25 was designed and synthesized with referenced to the structure of napabucasin, the minimal inhibitory concentrations (MICs) and the minimum bactericidal concentrations (MBCs) of LCG-N25 against Streptococcus mutans, Streptococcus sanguinis, and Streptococcus gordonii were evaluated by microdilution method. The antimicrobial activity of LCG-N25 was further evaluated by crystal violet staining, CFU counting, biofilm metabolism assay, dead/live fluorescent staining, and scanning electron microscopy (SEM). The effect of LCG-N25 on the extracellular polysaccharides (EPS) of biofilms was determined by both anthrone-sulfuric acid method and fluorescent staining. The microbial composition of streptococcal biofilms after LCG-N25 treatment was further visualized and quantified by fluorescent in situ hybridization (FISH). Besides, the cytotoxicity of LCG-N25 was evaluated by CCK-8 assay, and repeated exposure of S. mutans to LCG-N25 treatment was performed to assess if this novel compound could induce drug resistance of this cariogenic bacterium. We found that LCG-N25 exhibited a good antibacterial activity, low-cytotoxicity, and did not induce drug resistance of cariogenic S. mutans. These findings suggest that LCG-N25 may represent a promising antimicrobial agent that can be used as an adjuvant to the management of dental caries.